(untitled) (Revista Cocar, 2023)
The current research aimed to investigate the attitudes of Physical Education teachers in the last years of elementary school in the municipal education system in Manaus regarding the inclusion of students with disabilities. The methodology used is characterized as descriptive research with a qualitative and quantitative approach and included the participation of 102 Physical Education teachers from the last years of elementary school in the Municipal Education Department of Manaus (Secretaria Municipal de Educação de Manaus - SEMED) who answered the PEATID III questionnaire. The analysis of the results was performed using descriptive statistics, with the median as a measure of central tendency. The results indicate that, in general, teachers (52.9%) have favorable attitudes to the inclusion of students with disabilities in Physical Education classes. However, 47.1% were neutral to this process. Keywords: Attitude; Physical Education; Inclusive Education. Resumo A presente pesquisa teve como objetivo investigar as atitudes dos professores de Educação Física dos anos finais do ensino fundamental da rede municipal de ensino de Manaus em relação à inclusão de alunos com deficiência. A metodologia utilizada caracteriza-se como pesquisa descritiva com abordagem qualitativa e quantitativa e contou com a participação de 102 professores de Educação Física dos anos finais do ensino fundamental da Secretaria Municipal de Educação de Manaus (SEMED) que responderam ao questionário PATID III. A análise dos resultados foi realizada por meio de estatística descritiva, tendo a mediana como medida de tendência central. Os resultados indicam que, em geral, os professores (52,9%) têm atitudes favoráveis à inclusão de alunos com deficiência nas aulas de Educação Física. No entanto, 47,1% foram neutros a esse processo. Palavras-chave: Atitudes; Educação Física; Educação Inclusiva.